2015
DOI: 10.1111/jopy.12230
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Noncognitive, and Family Background Contributions to College Attainment: A Behavioral Genetic Perspective

Abstract: Objective There is considerable evidence that college attainment is associated with family background and cognitive and non-cognitive skills. Behavioral genetic methods are used to determine whether the family background effect is mediated through cognitive and non-cognitive skill development. Method We analyze data from two longitudinal behavioral genetic studies, the Minnesota Twin Family Study, consisting of 1382 pairs of like-sex twins and their parents, and the Sibling Interaction and Behavior Study, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 57 publications
2
44
1
Order By: Relevance
“…First, we tested whether the offspring’s education mediated the relation between parental education and offspring personality. Parental education is a strong predictor of offspring educational attainment: Offspring with parents who have more years of education are approximately 2–3 times more likely to graduate from college than offspring with parents who have less education (McGue, Rustichini, & Iacono, in press). To the extent that education is associated with specific traits (Mortensen et al, 2014), it may be one mechanism that accounts for part of the association between parental education and offspring personality.…”
Section: Introductionmentioning
confidence: 99%
“…First, we tested whether the offspring’s education mediated the relation between parental education and offspring personality. Parental education is a strong predictor of offspring educational attainment: Offspring with parents who have more years of education are approximately 2–3 times more likely to graduate from college than offspring with parents who have less education (McGue, Rustichini, & Iacono, in press). To the extent that education is associated with specific traits (Mortensen et al, 2014), it may be one mechanism that accounts for part of the association between parental education and offspring personality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that people with higher measurements of non-cognitive skills have better education, health and labour market outcomes (2)(3)(4)(5)(6)(7)(8). For example, Borghans and colleagues report that personality explains 16% of the variance in achievement scores in a US sample (8).…”
Section: Introductionmentioning
confidence: 99%
“…0.52 for digit span to 0.82 for reading) (16), and suggest that measurement error on non-cognitive skills may be relatively high (5). Modest correlations between different non-cognitive skills have been observed for a range of traits such as grit and conscientiousness (18); academic effort and academic problems (7); and internalising and externalising behaviours (19). The bulk of reported correlations between non-cognitive skills though have been small (7,18), supporting the multidimensionality of non-cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations